Kajian Angkutan Umum Sebagai Pendukung Kegiatan Di Wilayah Pedesaan Propinsi Banten - Setyabudi, Besar (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Typical of public transportation in Banten is dominated by small-mini bus with capacity of12 passengers. The system of this public transportation has already arranged by local government. The villagers usually waiting for this public transportation on the side of the street near their village since there is very rare ofbus stop in Province Banten. One of the most common transportation challenges today in Provision Banten is keeping up with the rapid villagers' population growth. This population growth directly affects existing public transportation capacity and congestion levels - which directly affects the distribution ofharvest since the congestion used to happened and seen in many street notfar from traditional market, school, hospital and some road travelled. Road safety has not seen aspriority for the public transportation in Banten, as it seen from the vehicles'feasibility, driver's behaveior that require regular supervise and from the passengers view as well since they tend to ignore the safety as long as their need of transportation fulfilled. The operational movement ofpublic transportation in Banten can be divided into three categories; based on time (busy time and unoccupied), purpose of travel (working, school, and shopping), and type of activity (eg: household business). Public transportation in Province of Banten serves two cities and four districts including 1.207 dependent villages, and reliant villages and any other kinds ofvillage. The result of this study is kind of recommendations for the regional government in order to improve the safety road moreover the quality ofpublic transportation service in Province ofBanten.